Corporate Social Responsibility in Islamic Banks of Bangladesh: A Trend Analysis - Md. Riazul Haque; Md. Manjurul Haque (Demak Universal Journal of Islam and Sharia, 2025)
Objective: The study aims to explore the sector-wise contributions to Corporate Social Responsibility activities by full-fledged Islamic banks of Bangladesh and Evaluate the consistency and effectiveness of CSR practices across different Islamic banks. Theoretical framework: The theoretical framework for this study is grounded in Stakeholder Theory and Islamic Ethical Principles, emphasizing the obligation of Islamic banks to uphold social justice, transparency, and community welfare. It explores how Shariah-compliant institutions integrate CSR into operations, guided by both religious values and stakeholder expectations and analyzes emerging trends in their CSR practices in Bangladesh. Literature review: The literature review includes data and publications central bank (Bangladesh Bank), academic papers, reports from Islamic banks, articles, and previous research studies, reputable news outlets, financial reports, and different publications from both government and non-governmental organizations involved in CSR initiatives of Bangladesh. Methods: This study utilizes CSR expenditure data from full-fledged Islamic banks, covering the period from (July to December) 2018 to 2022, sourced primarily from Bangladesh Bank publications. Tables, graphs, and charts will be employed to visually represent the data and support the interpretation of the findings. Results: The analysis reveals a steady increase in CSR expenditures and a growing emphasis on key sectors such as disaster management, healthcare education, etc. From 65.69 Crore BDT in 2018 (July- December) to 255.07 Crore BDT in 2022 (July- December), representing more than a quadrupling of the initial amount. Implications: These findings These findings provide important implications for stakeholders. The trend analysis of CSR practices in Islamic banks in Bangladesh indicates a steady yet encouraging development in their social responsibility efforts. While many banks are actively contributing to areas like charity, healthcare, and education, a truly comprehensive approach that reflects Islamic ethical principles and a focus on long-term sustainability is still missing. Novelty: The novelty of this study lies in its cross-biannual comparative approach and specific focus on the expenditure of full-fledged Islamic banks in corporate social responsibility, which has not been systematically studied in the context of Bangladesh.